Cooperative Bond Activation and Catalytic Reduction of Carbon Dioxide at a Group 13 Metal Center1. (27th February 2015) - Abdalla, Joseph A. B.; Riddlestone, Ian M.; Tirfoin, Rémi; Aldridge, Simon
Abstract A single‐component ambiphilic system capable of the cooperative activation of protic, hydridic and apolar HX bonds across a Group 13 metal/activated β‐diketiminato (Nacnac) ligand framework is reported. The hydride complex derived from the activation of H2 is shown to be a competent catalyst for the highly selective reduction of CO2 to a methanol derivative. To our knowledge, this process represents the first example of a reduction process of this type catalyzed by a molecular gallium complex.